2013
DOI: 10.1037/a0031440
|View full text |Cite
|
Sign up to set email alerts
|

Information content moderates positivity and negativity biases in memory.

Abstract: Two experiments examined the impact of encoding conditions and information content in memory for positive, neutral, and negative pictures. We examined the hypotheses that the positivity effect in memory (i.e., a bias in favor of positive or against negative information in later life) would be reduced when (a) pictures were viewed under structured as opposed to unstructured conditions, and (b) contained social as opposed to nonsocial content. Both experiments found that the positivity effect observed with nonso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 43 publications
7
35
0
Order By: Relevance
“…For pictures, self-referential processing increased old/new recognition of positive and neutral pictures, but only marginally for negative pictures. This pattern for pictures is consistent with the results of Hess et al (2013, Experiment 2) showing enhanced recall after self-referential encoding of positive, but not negative, social pictures. Taken together, these results are generally consistent with previous findings of an item SRE under various conditions.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For pictures, self-referential processing increased old/new recognition of positive and neutral pictures, but only marginally for negative pictures. This pattern for pictures is consistent with the results of Hess et al (2013, Experiment 2) showing enhanced recall after self-referential encoding of positive, but not negative, social pictures. Taken together, these results are generally consistent with previous findings of an item SRE under various conditions.…”
Section: Discussionsupporting
confidence: 90%
“…One notable exception is a study by D’Argembeau and colleagues (2005, Experiment 1) that showed a bigger SRE for the recall of positive than negative trait adjectives. To our knowledge, only one study has explicitly investigated the SRE using positive and negative pictures (Hess, Popham, Dennis, & Emery, 2013, Experiment 2). In contrast to the pattern found in trait adjective studies, Hess et al (2013) found that among social pictures (i.e., pictures that included people), self-referential encoding (i.e., imagining themselves, a close family member, or a friend in the situation depicted in the picture) significantly increased recall of positive pictures, but did not enhance recall of negative pictures; self-referential encoding did not enhance the recall of either positive or negative nonsocial pictures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Insight as to why the positivity effect was not demonstrated in the current study, despite instructions that placed few constraints on the memory retrieved, may be provided by recent research by Hess et al (2013). Hess et al presented both social and nonsocial pictures to participants and found evidence of the positivity effect in aging only regarding the rates of recall in nonsocial stimuli.…”
Section: Discussionmentioning
confidence: 48%
“…Nørby (2015) argues that the act of forgetting plays a vital role in maintaining mental wellbeing by limiting access to negative memories, promoting a positive outlook. Indeed, it appears positivity biases in memory are driven by top-down, goal-directed processes, with little evidence to suggest that the strength of such positivity biases is effected at memory encoding stages (Hess, Popham, Dennis, & Emery, 2013). Retrieval-Induced Forgetting (RIF), a phenomenon in which the selective retrieval of a particular memory trace causes the forgetting of another rival memory trace (Anderson, Bjork, & Bjork, 1994), has been put forward as a potential mechanism by which the positivity bias in memory occurs (Storm & Jobe, 2012).…”
Section: Introductionmentioning
confidence: 99%